Efektivitas Daun Binahong (Anredera scandens (L.)Moq) Sebagai Obat Penyembuhan Berbagai Luka :Review literature : Efektivitas Daun Binahong (Anredera scandens (L.)Moq) Sebagai Obat Penyembuhan Berbagai Luka - Rifa Musyaropah; Supriyatna, Ateng (An Idea Health Journal, 2023)
Wounds are damage to a network unit or component which results in a specific tissue substance being damaged or lost. Wound healing is the body's response when an injury occurs to various injuries with a complex regeneration process that can result in continuous restoration of anatomy and function. Binahong (Anredera scandens (L.) Moq.) is a typical Indonesian plant which is used to treat various kinds of diseases, one of which is to treat various kinds of wounds. This study used the literature review method, searched journals with the Google Schoolar database with inclusion and exclusion criteria for published articles between 2006-2023 and found 14 articles, but after filtering, 10 articles were finally discussed. Journals are selected using PRISMA. This research shows that several studies discussing the effect of binahong leaves on wound healing have proven to be effective for use and have the same effectiveness as other wound healing.